Leaf angle adjustment improves apparent covariation between fluorescence and photochemical quantum yields across leaves - Jongmin Kim; Audrey Root; Michael C. Benson; Daniel Beverly; Jennifer.E. Johnson; Manuel Lerdau; Richard P. Phillips; Kimberly A. Novick; Xi Yang (Remote Sensing of Environment, 2026)

Variable trade-offs in growth and reproduction: Comparative analysis of two oak species in Indiana, USA - Linnea S. Fraser; Justin T. Maxwell; Scott M. Robeson; Kim A. Novick; Grant L. Harley; Danielle Williams; Robert K. Swihart; Macarena Férriz; Joshua C. Bregy; Ben Lockwood (Dendrochronologia, 2026)

AmeriFlux: Its Impact on our understanding of the ‘breathing of the biosphere’, after 25 years - Dennis Baldocchi; Kim Novick; Trevor Keenan; Margaret Torn (Agricultural and Forest Meteorology, 2024)

A new empirical framework to quantify the hydraulic effects of soil and atmospheric drivers on plant water status - Maurizio Mencuccini; William R. L. Anderegg; Oliver Binks; Thorsten Knipfer; Alexandra G. Konings; Kim Novick; Rafael Poyatos; Jordi Martínez‐Vilalta (Global Change Biology, 2024)
Metrics to quantify regulation of plant water status at the daily as opposed to the seasonal scale do not presently exist. This gap is significant since plants are hypothesised to regulate their water potential not only with respect to slowly changing soil drought but also with respect to faster changes in air vapour pressure deficit (VPD), a variable whose importance for plant physiology is expected to grow because of higher temperatures in the coming decades. We present a metric, the stringency of water potential regulation, that can be employed at the daily scale and quantifies the effects exerted on plants by the separate and combined effect of soil and atmospheric drought. We test our theory using datasets from two experiments where air temperature and VPD were experimentally manipulated. In contrast to existing metrics based on soil drought that can only be applied at the seasonal scale, our metric successfully detects the impact of atmospheric warming on the regulation of plant water status. We show that the thermodynamic effect of VPD on plant water status can be isolated and compared against that exerted by soil drought and the covariation between VPD and soil drought. Furthermore, in three of three cases, VPD accounted for more than 5 MPa of potential effect on leaf water potential. We explore the significance of our findings in the context of potential future applications of this metric from plant to ecosystem scale.

A scalable framework for quantifying field-level agricultural carbon outcomes - Kaiyu Guan; Zhenong Jin; Bin Peng; Jinyun Tang; Evan H. DeLucia; Paul C. West; Chongya Jiang; Sheng Wang; Taegon Kim; Wang Zhou; Tim Griffis; Licheng Liu; et al. (Earth-Science Reviews, 2023)

Leaf angle as a leaf and canopy trait: Rejuvenating its role in ecology with new technology - Xi Yang; Rong Li; Andrew Jablonski; Atticus Stovall; Jongmin Kim; Koong Yi; Yixin Ma; Daniel Beverly; Richard Phillips; Kim Novick; Xiangtao Xu; Manuel Lerdau (Ecology Letters, 2023)
Life on Earth depends on the conversion of solar energy to chemical energy by plants through photosynthesis. A fundamental challenge in optimizing photosynthesis is to adjust leaf angles to efficiently use the intercepted sunlight under the constraints of heat stress, water loss and competition. Despite the importance of leaf angle, until recently, we have lacked data and frameworks to describe and predict leaf angle dynamics and their impacts on leaves to the globe. We review the role of leaf angle in studies of ecophysiology, ecosystem ecology and earth system science, and highlight the essential yet understudied role of leaf angle as an ecological strategy to regulate plant carbon–water–energy nexus and to bridge leaf, canopy and earth system processes. Using two models, we show that leaf angle variations have significant impacts on not only canopy‐scale photosynthesis, energy balance and water use efficiency but also light competition within the forest canopy. New techniques to measure leaf angles are emerging, opening opportunities to understand the rarely‐measured intraspecific, interspecific, seasonal and interannual variations of leaf angles and their implications to plant biology and earth system science. We conclude by proposing three directions for future research.

Separating the effects of climate and vegetation on evapotranspiration along a successional chronosequence in the southeastern US - PAUL C. STOY; GABRIEL G. KATUL; MARIO B. S. SIQUEIRA; JEHN‐YIH JUANG; KIMBERLY A. NOVICK; HEATHER R. McCARTHY; A. CHRISTOPHER OISHI; JOSHUA M. UEBELHERR; HYUN‐SEOK KIM; RAM OREN (Global Change Biology, 2006)
We combined Eddy‐covariance measurements with a linear perturbation analysis to isolate the relative contribution of physical and biological drivers on evapotranspiration (ET) in three ecosystems representing two end‐members and an intermediate stage of a successional gradient in the southeastern US (SE). The study ecosystems, an abandoned agricultural field [old field (OF)], an early successional planted pine forest (PP), and a late‐successional hardwood forest (HW), exhibited differential sensitivity to the wide range of climatic and hydrologic conditions encountered over the 4‐year measurement period, which included mild and severe droughts and an ice storm. ET and modeled transpiration differed by as much as 190 and 270 mm yr −1 , respectively, between years for a given ecosystem. Soil water supply, rather than atmospheric demand, was the principal external driver of interannual ET differences. ET at OF was sensitive to climatic variability, and results showed that decreased leaf area index ( L ) under mild and severe drought conditions reduced growing season (GS) ET (ET GS ) by ca. 80 mm compared with a year with normal precipitation. Under wet conditions, higher intrinsic stomatal conductance ( g s ) increased ET GS by 50 mm. ET at PP was generally larger than the other ecosystems and was highly sensitive to climate; a 50 mm decrease in ET GS due to the loss of L from an ice storm equaled the increase in ET from high precipitation during a wet year. In contrast, ET at HW was relatively insensitive to climatic variability. Results suggest that recent management trends toward increasing the land‐cover area of PP‐type ecosystems in the SE may increase the sensitivity of ET to climatic variability.